Tegami bachi, letter bee. Volume 16, Wuthering Heights - Asada, Hiroyuki, 1968-; Amtower, Rich (Shonen Jump manga., 2014)
"After years of searching, Zazie is on the trail of the Gaichuu that devoured his parents' hearts. But the hunt will force him to learn more about himself--and his past--than he ever imagined. And Emil, the kindly blind girl who runs the nearby inn, has an terrible secret-- from publisher's web site.